PENGEMBANGAN KUNCI DETERMINASI MYRIAPODA DALAM MODEL PEMBELAJARAN INQUIRY UNTUK MENINGKATKAN HASIL BELAJAR TAKSONOMI INVERTEBRATA MAHASISWA PRODI PENDIDIKAN BIOLOGI IKIP PGRI MADIUN SEMESTER GENAP 2013/2014 - Sri Utami; Arim Wahyu Novika Pradani; Soeprijadi Djoko Laksana (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
This study aims to develop a key book in the Myriapoda determination Inquiry learning model to improve learning outcomes and determine the feasibility Taxonomy Inveretebrata the book as a learning supporting Prodi Biology Education. The subjects that students Prodi Biology Education IIB half the number 12. Collecting data using multiple assessment sheet including key book appraisal determination Myriapoda, the student questionnaire responses, the performance test sheet, sheet cognitive test results, student activity sheets, and activity sheets lecturer. Analysis of the data using the average of each assessment. The result of this research is a key book Myriapoda determination developed with 4D models (Four D Models) with the stages of defining, designing, developing, while the spread was not done because of the larger scale. The results showed that 80% assessmentsupervisor and lecturer of Invertebrate Taxonomy courses give a good assessment can be categorized or fit for use Other research results are students responded positively to the book developed by providing an assessment that is equal to 70.8% agreed, and 22% strongly agreed, besides learning theInquiry model can improve the process and the results of this study demonstrated the value of cognitive test results the average is 80 so it can be categorized as good.